2014
DOI: 10.4081/ijfs.2014.4581
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella prevalence and microbiological contamination of pig carcasses and slaughterhouse environment

Abstract: In seven EC swine abattoirs Salmonella prevalence (ISO 6579/2002) and serotypes of 25 piglets, 61 finishing pigs (lymph nodes, colon content, carcass and liver surface) and slaughterhouse environments (scalding water, surfaces in contact with meat and not in contact with meat) were investigated. Moreover, aerobic colony count [total viable count (TVC); ISO 4833] and Enterobacteriaceae (ISO 21528-2) of piglets and finishing pigs’ carcasses were evaluated, and the results compared with EU process hygiene criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…To our knowledge, there are no official reported data about the prevalence of Salmonella at slaughterhouses or pork products at retail markets in the country, so this may be the first epidemiological study among the whole pork production chain in the region. When our results were compared with studies from other countries, the Salmonella prevalence at slaughterhouses was similar that observed in Vietnam (22%) but higher than reported in Naples (15.9%), Parma (10.9%) and Rio de Janeiro (10.5%) (Yokomo et al, 2016;Piras et al, 2014;Bonardi et al, 2013;Cabral et al, 2016). The Salmonella prevalence in pork sausage ("chorizo") at retail markets was consistent to other study in Brazil, with a similar pork production chain (26%) (Cabral et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, there are no official reported data about the prevalence of Salmonella at slaughterhouses or pork products at retail markets in the country, so this may be the first epidemiological study among the whole pork production chain in the region. When our results were compared with studies from other countries, the Salmonella prevalence at slaughterhouses was similar that observed in Vietnam (22%) but higher than reported in Naples (15.9%), Parma (10.9%) and Rio de Janeiro (10.5%) (Yokomo et al, 2016;Piras et al, 2014;Bonardi et al, 2013;Cabral et al, 2016). The Salmonella prevalence in pork sausage ("chorizo") at retail markets was consistent to other study in Brazil, with a similar pork production chain (26%) (Cabral et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…This result was expected as this serotype is well known to be adapted to pigs (Matiasovic et al ., 2014). In fact, it is one of the most common in slaughter pigs in Italy (Bonardi et al ., 2003 and 2016; Piras et al ., 2011 and 2014; Fois et al ., 2017; Pesciaroli et al ., 2017) and other European countries (Nollet et al ., 2004; Hauser et al ., 2011; Gomes-Neves et al ., 2012; Kerouanton et al ., 2013; Sanchez- Rodriguez et al ., 2018). Moreover, S .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the total number of bacteria (log CFU / cm2) obtained after disinfection of the hook and meat knife indicate that the professional veterinarian properly carried out all the disinfection phases, as well as the disinfection itself, since the total number of bacteria was significantly lower (p <0.01) during the course of all five weeks, in relation to the number of bacteria after disinfection by an unprofessional person. Properly conducted disinfection and replacement of knives during work are very important because studies have shown that the most common way of meat contamination is with dirty hands and dirty tools (Haileselassie et al, 2013;Piras at al., 2014;Abdalla et al, 2009;Svobodová et al, 2012;Gun et al, 2003). In the slaughterhouses the knives are washed in a traditional manner by rinsing with water at a temperature of 20˚-40˚C, followed by a brief immersion in a bath (sterilizer) in which the water temperature is below 82˚C (EC Regulation 853/2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that the usual cleaning and disinfection of the lairage were not sufficient to eliminate this risk, whereas an improved procedure for cleaning and disinfection was still unsatisfactory. In the literature, most authors point to the fact that a significant reduction in the level of microorganisms in the slaughterhouses can be achieved only when effective sanitary washing with hot water is carried out prior to disinfection (Piras at al., 2014;McDowell et al, 2007;Rajkowski et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation